037 Differences in the Gut Microbiome Composition Between Men with Erectile Dysfunction and a Matched Cohort: A Pilot Study. (1st May 2022) - Osman, M.M.; El-Khatib, F.M.; Dianatnejad, S.; Nguyen, J.; Choi, E.; Towe, M.; Yafi, F.A.
ABSTRACT: Introduction: The gut microbiome (GM) plays an important role in human health, ranging from supplying essential nutrients, synthesizing vitamin K, to promoting angiogenesis and enteric nerve function. It has also been recently associated with a variety of chronic health conditions. To date, however, there have been no studies that have attempted to establish any association between the GM and erectile dysfunction (ED). Objective: To analyze stool samples from patients with ED and compare them to matched controls for differences in their GM. Methods: We collected stool samples from 37 patients with ED and matched them with 37 controls. All samples were processed by a third-party company, Viome Inc. The samples were analyzed by metatranscriptome sequencing which allows for data to show both the taxonomy of the microbiome and its KEGG orthology (KO). We compared richness, prevalence and expression of the taxa and KOs between the ED and control groups. Results: There were 224 species (16.85%) with significantly differential prevalence and 135 species (10.31%) with significantly differential expression. There were 565 KOs (10.42%) with significantly differential prevalence and 653 KOs (12.05%) with significantly differential expression. Richness is the number of microbial species detected in a sample. Diversity assesses the abundance and evenness of a species to assess how diverse an individual sample is. The ED group demonstrated significantly lower taxonomic richness and diversity, p= 1.33 x 10^-5 (see figure below). Conclusions: This is the first study to look at associations between the GM and ED. Patients with ED have significantly lower taxonomic richness and diversity. Further analyses are needed to better understand the implications of these findings and uncover potential targets for early targeted treatment or prevention of ED. Disclosure: Work supported by industry: yes, by Viome Inc.. A consultant, employee (part time or full time) or shareholder is among the authors (Antares. Clarus. Coloplast. Promescent.).